2011
DOI: 10.1166/jnn.2011.3772
|View full text |Cite
|
Sign up to set email alerts
|

TiB2 Nanostructured Coating for GFRP Injection Moulds

Abstract: O PDF relativo ao artigo que solicita, não se encontra disponível em Acesso Aberto. Motivos: O editor não permite o depósito e disponibilização em acesso aberto do PDF que solicita. Para consultar o documento deve aceder ao endereço do editor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…4. Critical load values obtained are typical for industrial applications, being close to those found by some authors [7][8][9] for other PVD sputtered coatings. One of the most important parameters for tribological applications is the hardness.…”
Section: Resultssupporting
confidence: 88%
“…4. Critical load values obtained are typical for industrial applications, being close to those found by some authors [7][8][9] for other PVD sputtered coatings. One of the most important parameters for tribological applications is the hardness.…”
Section: Resultssupporting
confidence: 88%
“…Ion implantation and unbalanced magnetron sputtering PVD (Bienk & Mikkelsen, 1997), High Velocity Oxy Fuel (HVOF) and Atmospheric Plasma Spraying (APS) (Gibbons & Hansell, 2008), diamond-like carbon and silicon carbide (Griffiths et al, 2010), nanostructured TiB2 (Martinho et al, 2011), Oxide coating (Alumina) and Nitride coatings (AlN, CrN, NiCr(N), TiN) (Navabpour et al, 2006), among other surface engineering coating have been tested in order to evaluate their performance to avoid molding surface wear and assist the demolding process.…”
Section: Surface Engineering In Molding Toolsmentioning
confidence: 99%
“…Nowadays, increasing requirements demanded by designers have driven the use of short glass fibers as reinforcements in many parts, namely for the automotive industry. Abrasion is a typical phenomenon in the plastic injection moulding process and it becomes even more important when plastics are reinforced with glass fibres [1][2][3][4][5]. Otherwise, maintenance operations related to moulds represent the costs and inactivity periods of the mould which affect the competitiveness of the process and are strongly connected to the concept of the life cycle cost [6].…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome these problems, some authors have investigated a diversified number of surface treatments and tribological coatings [1][2][3]5,[15][16][17][18][19][20]. In fact, recent developments in coatings technology allow a multifaceted approach to each problem, using mono-or multilayered coatings, single composition or graded layers, conventional or nanostructured films.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation